La subsistance de l'homme. La place de l'économie dans l'histoire et la société - Praquin, Nicolas (Comptabilité Contrôle Audit, 2012)
Keywords: La subsistance de l'homme: La place de l'économie dans l'histoire et la société (Book); POLANYI, Karl, 1886-1964; The Livelihood of Man; book review; economic development; nonfiction

How to conceptualize an alternative to platform capitalism according to the re-embedding process of K. Polanyi ? [Comment penser l'alternative au capitalisme de plateforme dans une logique de réencastrement polanyien ?] - Aufrère, Laura; Eynaud, Philippe; Maurel, Lionel; Vercher-Chaptal, Corinne (CEPN Working Papers, 2020)
The article considers alternatives to platform capitalism in a logic of Polanyian re-embedding. Stemming from case studies in the car-pooling, delivery and hosting sectors, the results uncover hybrid business models in which the market principle is used in the service of reciprocal logic. Rejecting the formal algorithmic rationality of capitalist platforms, the alternatives seek to align individual and collective behavior with values of solidarity and goals of general interest. They are experimenting with original methods of scaling up, based on the federation of communities, respectful of their anchoring in the substantive economy. The results make it possible to think of complementarities between different forms of embedding likely to be played out on several scales, and open perspectives for rethinking public policies vis-à-vis the experiments of the solidarity economy and the commons.
Keywords: coopérativisme de plateforme; decommodification; digital platforms; démar- chandisation; plateformes numériques; platform cooperativism; re-embedding; reciprocity; ré-encastrement; réciprocité; substantive economy; économie substantive